Pernikahan Beda Agama Dalam Perspektif Hukum Keluarga Islam: Analisis Konsep Ahli Kitab Dan Implementasinya Terhadap Umat Nasrani Dan Yahudi - Akel Pernando; Khairil Anwar; Muslih Muslih (Maqasid: Jurnal Studi Hukum Islam, 2025)
This study examines interfaith marriage from the perspective of Islamic family law, specifically focusing on the concept of Ahl al-Kitab (People of the Book) and its implementation regarding Christians and Jews. The research aims to analyze the legal framework governing interfaith marriages in Islamic jurisprudence and examine the contemporary application of these principles in modern Muslim societies. Using a normative-juridical approach with qualitative descriptive methods, this study analyzes classical and contemporary Islamic legal sources alongside modern scholarly interpretations. The findings indicate that Islamic law permits Muslim men to marry women from Ahl al-Kitab under specific conditions, while maintaining strict guidelines to preserve religious integrity. However, significant scholarly debate exists regarding the contemporary definition of Christians and Jews as legitimate Ahl al-Kitab, particularly concerning theological differences between early Christian communities and modern denominations. The study concludes that while the Quranic permission remains valid, practical implementation requires careful consideration of contemporary religious contexts and the maintenance of Islamic principles in family life. Keywords: Interfaith Marriage, Ahl al-Kitab, Islamic Family Law, Christians, Jews